2002
DOI: 10.1006/dbio.2002.0581
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BMP Activity by the FGF Signal Promotes Posterior Neural Development in Zebrafish

Abstract: The expression patterns of region-specific neuroectodermal genes and fate-map analyses in zebrafish gastrulae suggest that posterior neural development is initiated by nonaxial signals, distinct from organizer-derived secreted bone morphogenetic protein (BMP) antagonists. This notion is further supported by the misexpression of a constitutively active form of zebrafish BMP type IA receptor (CA-BRIA) in the zebrafish embryos. It effectively suppressed the anterior neural marker, otx2, but not the posterior mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 78 publications
5
71
0
Order By: Relevance
“…It has recently been shown that the pharynx of cnidarians asymmetrically expresses several of the genes found in the vertebrate "organizer", including TGF-β antagonists NvNoggin1 and NvFollistatin and a transcription factor NvGsc (Matus et al 2006a), and that some of these genes are also expressed at the aboral pole at the base of the apical tuft, a chemosensory structure . FGF signaling alone in ascidians (Bertrand et al 2003;Miya and Nishida 2003) or together with TGF-β antagonism in vertebrates (De Robertis and Kuroda 2004;Delaune et al 2005;Koshida et al 2002) coordinate neural induction. It seems likely then that the expression of FGF signaling pathway genes in the pharynx and apical tuft may to be playing a role in neural induction in N. vectensis.…”
Section: A Role For Fgfs In Neural Induction In Cnidariansmentioning
confidence: 99%
“…It has recently been shown that the pharynx of cnidarians asymmetrically expresses several of the genes found in the vertebrate "organizer", including TGF-β antagonists NvNoggin1 and NvFollistatin and a transcription factor NvGsc (Matus et al 2006a), and that some of these genes are also expressed at the aboral pole at the base of the apical tuft, a chemosensory structure . FGF signaling alone in ascidians (Bertrand et al 2003;Miya and Nishida 2003) or together with TGF-β antagonism in vertebrates (De Robertis and Kuroda 2004;Delaune et al 2005;Koshida et al 2002) coordinate neural induction. It seems likely then that the expression of FGF signaling pathway genes in the pharynx and apical tuft may to be playing a role in neural induction in N. vectensis.…”
Section: A Role For Fgfs In Neural Induction In Cnidariansmentioning
confidence: 99%
“…In this respect, it is important to note that the growth medium used contains EGF, IGF1, and basic FGF as part of a commonly used mixture of factors that promote neurosphere formation (21,35). Particularly, interplay between FGF-induced suppression of BMPs, which often antagonize during embryonic development (36,37), might play a role in promoting neurosphere formation from CN cells. This hypothesis is supported by our observation that inhibition of FGF signaling virtually abolished neurosphere formation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to wildtype and fgf17b-injected embryos, some of affected embryos that were coinjected with fgf17 mRNA and sp5l-MO showed weaker expression though the expression domain still shifted anteriorly and expanded ventrally. rior neuroectodermal fate upon overexpression in zebrafish embryos (Koshida et al, 2002;Kudoh et al, 2002;Cao et al, 2004;Rentzsch et al, 2004). We re-investigated effects of Fgf signaling on the anteroposterior neuroectodermal patterning by overexpressing fgf17b, which has a strong neuroectodermal posteriorizing activity (Cao et al, 2004).…”
Section: Fgf Signaling Posteriorizes the Neuroectodermmentioning
confidence: 99%
“…These data further support the notion that sp5l plays a role in mediating Fgf activity in the anteroposterior patterning of the neuroectoderm. sp5l is Required for fgf8 and fgf3 Expression in the Hindbrain During Gastrulation fgf3 and fgf8 are expressed in the forebrain and hindbrain during and after gastrulation in zebrafish embryos (Reifers et al, 1998;Phillips et al, 2001), and they play important roles in the formation and patterning of the forebrain and hindbrain (Reifers et al, 1998;Shinya et al, 2001;Koshida et al, 2002;Maves et al, 2002;Walshe et al, 2002;Walshe and Mason, 2003). Given that sp5l is expressed in the posterior neuroectoderm during gastrulation (Zhao et al, 2003), we asked whether it is required for expression of fgf3 and fgf8 in the hindbrain.…”
Section: Overexpression Of Sp5l Rescues Effects Of Xfd On Neuroectodementioning
confidence: 99%
See 1 more Smart Citation